A Secure Private Key Recovery Based on DNA Bio-Cryptography for Blockchain - Al-karkhi, Asia Ali Salman; Hassan, Nidaa Flaih; Azeez, Raghad Abdulaali (Iraqi Journal of Science, 2023)
The existence of the Internet, networking, and cloud computing support a wide range of new technologies. Blockchain is one of these technologies; this increases the interest of researchers who are concerned with providing a safe environment for the circulation of important information via the Internet. Maintaining solidity and integrity of a blockchain’s transactions is an important issue, which must always be borne in mind. Transactions in blockchain are based on use of public and private keys asymmetric cryptography. This work proposes usage of users’ DNA as a supporting technology for storing and recovering their keys in case those keys are lost — as an effective bio-cryptographic recovery method. The RSA private key is responsible for maintaining the authenticity of the blocks’ wallets throughout any transaction related to any block of the blockchain. This framework can be used for a wide range of applications such as student registration systems at universities: in order to prevent the forging of student graduation certificates. The experimental results demonstrated robustness of the proposed solution, using a number of key sizes. The effectiveness of our approach is compared to that of elliptic curve cryptography keys. Our approach shows that the security and authentication needed for blockchain technology can be accomplished using DNA combined with an RSA private key. On the other hand, the standard EC cryptography shows poor performance against our suggested method as demonstrated in the discussion section.